Mitral valve posterior leaflet reconstruction using extracellular matrix: an acute porcine study. (19th April 2018) - Tjørnild, Marcell J; Skov, Søren N; Poulsen, Karen B; Sharghbin, Mona; Benhassen, Leila L; Carlson Hanse, Lisa; Waziri, Farhad; Røpcke, Diana M; Nielsen, Sten L; Hasenkam, J Michael
Abstract: OBJECTIVES: To investigate mitral valve posterior leaflet and subvalvular reconstruction using a 2-ply small intestinal submucosal extracellular matrix sheet. METHODS: Mitral valve posterior leaflet and subvalvular reconstruction was characterized in an acute 80-kg porcine model with 7 pigs acting as their own controls. The characterization was based on pressure catheter measurements of pressure differences to identify mitral regurgitation, stenosis and systolic anterior motion. Furthermore, echocardiography was used for the evaluation of leaflet mobility and geometry, whereas sonomicrometry was used to describe annular and subvalvular geometry. RESULTS: The reconstructed mitral valve was fully functional without any signs of regurgitation (peak left atrial pressure for baseline and reconstruction 12 ± 2 mmHg vs 11 ± 2 mmHg, P  = 0.550), mitral valve stenosis (mean pressure difference across the mitral valve 4.8 ± 2.3 mmHg vs 4.1 ± 2.3 mmHg, P  = 0.589) or systolic anterior motion. The echocardiographic characterization revealed septal–lateral downsizing, reduced tenting area, increased coaptation length (6.0 ± 0.6 mm vs 8.7 ± 2.3 mm, P  = 0.002) and an atrial bend of the reconstructed posterior leaflet. A ballooning effect of the patch material was present at the posterior annular segment. CONCLUSIONS: Mitral valve posterior leaflet and subvalvular reconstruction using a 2-ply small intestinal submucosal extracellular matrix sheet as patch material was possible in an acute porcine model. The reconstructed mitral valve was fully functional without signs of mitral valve stenosis, valve regurgitation, stenosis or systolic anterior motion. The ballooning appearance of the patch material might, however, constitute an altered leaflet stress distribution in this area.